The Professionalism of Islamic Education Teachers In Learning Management - Mansir, Firman; Musadad, Irfan (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
This study aims to explain the professional attitude of Islamic Religious Education teachers in regulating learning, especially during the Covid-19 pandemic. A professional teacher is always reflected in all his activities as a person who constantly manages and develops educational institutions. This research uses a qualitative approach, so that in collecting data using the literature study method sourced from various references both from journal articles and research books published in 2015-2022 and the focus of research in Indonesia as a whole. The results of this study show that the professionalism of PAI teachers can be seen from their concern and seriousness in managing madrasahs, through teaching that is carried out with full responsibility, empathy, a sense of belonging, and making students like their own children, especially when entering the era of the Covid-19 pandemic. In addition, PAI can encourage students to advance and develop in terms of ability and creativity for a better future in the context of society. This is done when learning takes place using a humanist approach, the essence of which is to build the creativity of students with humanist traits. Thus, PAI teachers in madrasas can be examples of self-identification centers and consultants for students to have sensitivity to various sources of knowledge. Keywords: Teachers, Islamic Religious Education, Education Management